Anxiety level and basic hope in participants to eight-day-long “ignatian” retreats - Wilczek, Cezary (Studia Psychologica: Theoria et praxis, 2009)
The article analyses the ways in which “Ignatian” retreats as a form of silent prayer influence the participants’ anxiety level and basic hope. The aim of this empirical study is to analyse the changes in the level of the studied variables and their interdependence. The study group (N=6l) was composed by participants to “Ignatian” retreats, their ages ranging from 24 to 56. The research conducted has confirmed the initial hypotheses, pointing out the occurrence of statistically significant connections between anxiety and basic hope, showing the strength of dependence between them. We can, therefore, draw conclusions supporting and extending the so far theories to be found in the relevant literature on this issue.